Fatal Renal Failure in a Spinal Cord Injury Patient with Vesicoureteric Reflux Who Underwent Repeated Ureteric Reimplantations Unsuccessfully: Treatment Should Focus on Abolition of High Intravesical Pressures rather than Surgical Correction of Reflux - Subramanian Vaidyanathan; Bakul Soni; Kottarathil Abraham Abraham; Peter Hughes; Gurpreet Singh (Case Reports in Urology)
A 29-year-old man developed paraplegia at T-10 level due to road traffic accident in 1972. Both kidneys were normal and showed good function on intravenous urography. Division of external urethral sphincter was performed in 1973. In 1974, cystogram showed retrograde filling of left renal tract, which was hydronephrotic. Left ureteric reimplantation was performed. Following surgery, cystogram revealed marked retrograde filling of left renal tract as before. Penile sheath drainage was continued. In 1981, intravenous urography revealed bilateral severe hydronephrosis. Left ureteric reimplantation was performed again in 1983. Blood pressure was 220/140 mm Hg; this patient was prescribed atenolol. Cystogram showed gross left vesicoureteral reflux. Intermittent catheterisation was commenced in 2001. In 2007, proteinuria was 860 mg/day. This patient developed progressive renal failure and expired in 2012. In a spinal cord injury patient with vesicoureteral reflux, the treatment should focus on abolition of high intravesical pressures rather than surgical correction of vesicoureteric reflux. Detrusor hyperactivity and high intravesical pressures are the basic causes for vesicoureteral reflux in spinal cord injury patients. Therefore, it is important to manage spinal cord injury patients with neuropathic bladder by intermittent catheterisations along with antimuscarinic drug therapy in order to abolish high detrusor pressures and prevent vesicoureteral reflux. Angiotensin-converting enzyme inhibitors or angiotensin-receptor-blocking agents should be prescribed even in the absence of hypertension when a spinal cord injury patient develops vesicoureteral reflux and proteinuria.